The influence of serum Sterol Sulfotransferase, ANGPTL8, and SDC1 on liver function in patients with intrahepatic cholestasis during pregnancy: Serum Sterol Sulfotransferase, ANGPTL8, and SDC1 on liver function in intrahepatic cholestasis - Wang, Qixin; Wang, Ming; Wu, Wenqi (Journal of Medical Biochemistry, 2026)
[Objective] To explore the relationships between serum Sterol Sulfotransferase, Recombinant Angiopoietin Like Protein 8 (ANGPTL8), and Recombinant Syndecan (SDC1) and liver function in patients with intrahepatic cholestasis of pregnancy (ICP), as well as their influence on perinatal outcomes.[Methods] The control group consisted of 200 healthy pregnant women who had physical tests over the same time period, while the study group consisted of 210 ICP patients who were admitted to our hospital between June 2023 and December 2024.  The study group's and the control group's serum Sterol Sulfotransferase, ANGPTL8, SDC1, and liver function markers were compared. Pearson correlation analysis was used to analyze the correlations between the levels of serum Sterol Sulfotransferase, ANGPTL8, and SDC1 and various liver function indicators. The patients in the study group were divided into a poor outcome group (86 patients) and a good outcome group (124 patients) according to perinatal outcomes. Serum Sterol Sulfotransferase, ANGPTL8, and SDC1 levels were examined between the groups with negative and positive outcomes. The factors predicting unfavorable perinatal outcomes in patients with ICPs were examined using univariate and multivariate logistic regression analysis.[Results] Despite having a lower serum Sterol Sulfotransferase level, the study group had higher levels of ANGPTL8 and SDC1 than the control group. P
Keywords: Intrahepatic cholestasis of pregnancy; Proteoglycan-1; Liver function; Sterol Sulfotransferase; Recombinant Angiopoietin Like Protein 8